Трактування педагогічної культури особистості у наукових дослідженнях - Лащівська, Яна (My University, 2019)
У статті з’ясовано, що культура являє собою нормативні вимоги до будь-якої діяльності людини, а тому існує стільки видів культури, скільки видів самої людської діяльності. Тому виділення педагогічної культури в спеціальний об'єкт розгляду нам здається теоретично коректним. У педагогічній культурі втілені історично перевірені передові традиції педагогічної науки й практики. Мета статті - на основі теоретичного аналізу досліджуваної проблеми та вивчення освітньої практики проаналізувати та схарактеризувати сучасні наукові підходи педагогічної культури. Методи теоретичні – аналіз психолого-педагогічної, науково-методичної літератури для визначення сутності і змісту педагогічної культури. Результати роботи. Підґрунтям педагогічної культури служить загальна культура - рівень освіти, характер світогляду, ставлення до праці, загальна вихованість, коло інтересів і запитів, норми повсякденної поведінки. The article clarifies that culture is a normative requirement for any human activity, and therefore there are so many types of culture as many kinds of human activity itself. Therefore, the allocation of pedagogical culture in a special object of consideration seems to us theoretically correct. In the pedagogical culture, historically proven advanced traditions of pedagogical science and practice are embodied. The purpose of the article - on the basis of theoretical analysis of the problem under study and the study of educational practice, to analyze and characterize the modern scientific approaches of pedagogical culture. Theoretical methods - analysis of psychological and pedagogical, scientific and methodical literature for the definition of the essence and content of pedagogical culture. Results of work The basis of pedagogical culture is the general culture - the level of education, the nature of the worldview, attitude to work, general education, the range of interests and requests, the rules of everyday behavior. Pedagogical culture is considered at different levels: scientific and pedagogical, social-pedagogical, professional-pedagogical and personal. At the scientific and pedagogical level, pedagogical culture acts as an integral part of universal and national culture and covers the field of pedagogical values ​​that include scientific theories, pedagogical consciousness and thinking, and examples of practical cultural activities. Socio-pedagogical culture functions as a means of pedagogy of the surrounding reality. In the context of vocational and pedagogical level, pedagogical culture is considered as a sphere of professional activity that covers the requirements of society at one or another stage of its development, the laws of cultural and professional identification of the teacher. Pedagogical culture is often viewed as a personal characteristic of a teacher.
Keywords: педагогічна культура; pedagogical culture; особистість; personality; pedagogical skill; педагогічна майстерність; компетентність; організованість в діяльності; competence; organization in activity